2016
DOI: 10.5812/ircmj.24847
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Empathy Training on the Empathic Skills of Nurses

Abstract: BackgroundThe profound impact of empathy training on quality nursing care has been recognized. Studies have shown that there has been little improvement in nurses’ communication skills, and that they should work to enhance this area. Relevant training will lead to an improvement in nurses’ empathic skills, which in turn, will enable them to understand their patients better, establish positive interpersonal relationships with them, and boost their professional satisfaction.ObjectivesTo reveal the effect of empa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 27 publications
6
36
0
10
Order By: Relevance
“…Empathy is considered as an essential prerequisite for a nurse to effectively care for a patient and for a holistic understanding of a patient's perspective in a student population [5]. Authors of the study titled "The Effect of Empathy Training of the Empathic Skills of Nurses" stated that profound impact of empathy training on quality of nursing care has been recognized and relevant training will lead to an improvement in nurses' empathic skills, which in turn, will enable them to understand their patients better, establish positive interpersonal relationships with them, and boost their professional satisfaction, but when they held an experiment with training, after the training, no statistically significant difference was found (p = 0.886) [6]. In our experiment, which was similar we get results showing statistical significance at the level p = 0.01 after successful completion of the course of Professional Ethics (p = 0.008), Law and Legislation in Health Care (p = 0.003) and psychology (p = 0.007).…”
Section: Resultsmentioning
confidence: 99%
“…Empathy is considered as an essential prerequisite for a nurse to effectively care for a patient and for a holistic understanding of a patient's perspective in a student population [5]. Authors of the study titled "The Effect of Empathy Training of the Empathic Skills of Nurses" stated that profound impact of empathy training on quality of nursing care has been recognized and relevant training will lead to an improvement in nurses' empathic skills, which in turn, will enable them to understand their patients better, establish positive interpersonal relationships with them, and boost their professional satisfaction, but when they held an experiment with training, after the training, no statistically significant difference was found (p = 0.886) [6]. In our experiment, which was similar we get results showing statistical significance at the level p = 0.01 after successful completion of the course of Professional Ethics (p = 0.008), Law and Legislation in Health Care (p = 0.003) and psychology (p = 0.007).…”
Section: Resultsmentioning
confidence: 99%
“…In general, studies show an increased empathic thinking and empathic skills as a result of higher levels of education and experience . For example, in a study conducted on nurses, empathic skills were determined to increase according to the education level of nurses . A study of nurses who provided child care services found a significant relationship between the level of education and empathy skills .…”
Section: Discussionmentioning
confidence: 99%
“…31 For example, in a study conducted on nurses, empathic skills were determined to increase according to the education level of nurses. 32 A study of nurses who provided child care services found a significant relationship between the level of education and empathy skills. 33 Also, a significant increase in the empathic tendency scores was observed with an increase in the level of education in a study conducted on teachers with graduate and master's degree.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, it is stated that creative drama is effective in the development of social skills (Sullivan and Fulton, 2003). Kahriman et al (2016) stated that drama based activities affected the empathic tendencies of nurses. However, there are no studies which investigated empathic tendencies, communication skills of critical thinking of physiotherapy students and the effects of creative drama on these.…”
Section: Objectivesmentioning
confidence: 99%